2017
DOI: 10.1002/cmdc.201700295
|View full text |Cite
|
Sign up to set email alerts
|

A Hollow NaGdF4/AFn Nanosystem Based on “Relay Race” Release for Therapy

Abstract: To develop a multifunctional nanomaterial for dual‐mode imaging and synergetic chemotherapy, curcumin (CUR) was physically entrapped into hollow upconversion NaGdF4 nanomaterial, then apoferritin (AFn) loaded with doxorubicin (DOX) was attached to the NaGdF4 surface. Subsequent modification with the targeting reagent folic acid (FA) led to generation of the CUR/NaGdF4–DOX/AFn–FA conjugate for cancer treatment. X‐ray diffraction, scanning (SEM) and transmission electron microscopy (TEM), and Fourier transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Zhou et al described UCNPs integrated with apoferritin that achieved both dual mode imaging along with dual drug delivery. [ 104 ] Gadolinium‐based hollow mesoporous structured UCNPs (NaGdF 4 ) have been synthesized by a hydrothermal process. These nanoparticles exhibited good dispersion in an aqueous environment as well as enhanced upconversion fluorescence.…”
Section: Strategies For Targeting the Tmementioning
confidence: 99%
“…Zhou et al described UCNPs integrated with apoferritin that achieved both dual mode imaging along with dual drug delivery. [ 104 ] Gadolinium‐based hollow mesoporous structured UCNPs (NaGdF 4 ) have been synthesized by a hydrothermal process. These nanoparticles exhibited good dispersion in an aqueous environment as well as enhanced upconversion fluorescence.…”
Section: Strategies For Targeting the Tmementioning
confidence: 99%
“…In another words, weakening of intermolecular hydrogen bonds between hydrogen of hydroxyl groups in Epr molecules and amino groups in the internal structure of HsAFr, causing numerous Epr molecules to release inside dialysis bag, leading to a high concentration of Epr drug in the dialysis buffer [30]. Zhou et al also reported similar results for fast doxorubicin release from HsAFr nanocarrier at first 10 h [48]. The inner surface of HsAFr is rich in acidic residues (Glu and Asp), resulting in a high negative charge density located at the inner cavity of HsAFr nanocage.…”
Section: Determination Of Ee and DLmentioning
confidence: 76%